2009
DOI: 10.1016/j.chemosphere.2008.11.083
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between estrogenic chemicals in binary mixtures investigated using vitellogenin induction and factorial analysis

Abstract: a b s t r a c tConsiderable progress has been made in assessing the combined effects of chemicals, but the effect of mixtures remains one of the most daunting challenges in environmental toxicology. In this study, the effects of binary mixtures of estrogenic chemicals were investigated using plasma vitellogenin (VTG) induction in male adult Japanese medaka (Oryzias latipes) as the endpoint. We focused on whether or not the factorial design using rigorous statistical methods was appropriate for the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…Although the paper was retracted the following year because the result was lack of reproducibility in other laboratories (McLachlan, 1997), it led to academic concern and intense follow-up research. There have been lots of researches to study the effects of estrogenic mixtures on organisms ranging from recombinant yeasts and estrogen-sensitive cells (Arnold et al, 1997;Payne et al, 2001;Rajapakse et al, 2004;Silva et al, 2011Silva et al, , 2002Suzuki et al, 2001) to vertebrates such as fish and mice (Brian et al, 2007;Ramamoorthy et al, 1997;Ribeiro et al, 2012;Sun et al, 2009;Thorpe et al, 2005;Tinwell and Ashby, 2004). Among these test organisms, the recombinant human ER gene yeast obtained wide application because it provided not only fast and sensitive detection but also single MoA and ToA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the paper was retracted the following year because the result was lack of reproducibility in other laboratories (McLachlan, 1997), it led to academic concern and intense follow-up research. There have been lots of researches to study the effects of estrogenic mixtures on organisms ranging from recombinant yeasts and estrogen-sensitive cells (Arnold et al, 1997;Payne et al, 2001;Rajapakse et al, 2004;Silva et al, 2011Silva et al, , 2002Suzuki et al, 2001) to vertebrates such as fish and mice (Brian et al, 2007;Ramamoorthy et al, 1997;Ribeiro et al, 2012;Sun et al, 2009;Thorpe et al, 2005;Tinwell and Ashby, 2004). Among these test organisms, the recombinant human ER gene yeast obtained wide application because it provided not only fast and sensitive detection but also single MoA and ToA.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported adverse effects when fish were exposed to low concentrations of steroidal estrogens. These effects include increased plasma vitellogenin concentrations in males, increased rates of intersex, altered behavioral responses and decreased reproductive success (Panter et al, 1998;Imai et al, 2007;Zha et al, 2008;Sun et al, 2009;Hyndman et al, 2010). In particular, feminization of male fish due to long term exposure to low concentrations of steroids in aquatic environments has caused great concern throughout the world (Vethaak et al, 2005;Randak et al, 2009;Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…All of them are released to the environment via different sources and are presented simultaneously instead of separately. Thus, these chemicals not only have adverse effects on organisms at very low-level exposure (Myers et al, 2009), but also have the potential of additive or even synergistic effects when acting in combination (Kunz and Fent, 2006;Sun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%